Making schools smarter a system for monitoring school and district progress - Leithwood, Kenneth A.; Aitken, Robert 1934- (Corwin Press, Inc., 1995)
Leithwood and Aitken have created a handbook for developing a system of collaborative assessment, strategic planning, and accountability in schools and districts. This book supplies not only the instruments to obtain data on how well schools and districts are achieving their purposes but also a means by which to establish achievable standards of expectation. The authors' research included studies of Canadian and American schools and involved the participation of district personnel, teachers, students, parents, and board members. The authors used a real school to help them develop their model of an "ideal school" for the year 2000. Using this experimental model as a basis, they describe specific features to be found in an ideal school and present ways to measure comparable features of existing schools and districts. They provide guidelines for using data generated in these assessments to help move schools toward the ideal.